2020
DOI: 10.1002/cne.25031
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic innervation of inguinal white adipose tissue in the mouse

Abstract: Adipose tissue plays an important role in metabolic homeostasis and its prominent role as endocrine organ is now well recognized. Adipose tissue is controlled via the sympathetic nervous system (SNS). New viral, molecular-genetic tools will soon allow a more detailed study of adipose tissue innervation in metabolic function, yet, the precise anatomical extent of preganglionic and postganglionic inputs to the inguinal white adipose tissue (iWAT) is limited. Furthermore, several viral, molecular-genetic tools wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 46 publications
3
31
1
Order By: Relevance
“…This has allowed us to further our understanding of scWAT in mice by characterizing the innervation that exists within this tissue with greater scrutiny, demonstrating neurovascular interactions, parenchymal innervation, neuroimmune interactions, and neuro-adipose connections. It has been demonstrated previously that the neurites innervating scWAT branch from the same NBs that lead to the skin (Huesing et al, 2021), but we and others have clearly demonstrated that axon endings do terminate inside the parenchyma of scWAT. For the first time, we reveal a terminal junction of axons in scWAT, which we call the neuro-adipose nexus.…”
Section: Articlecontrasting
confidence: 42%
See 1 more Smart Citation
“…This has allowed us to further our understanding of scWAT in mice by characterizing the innervation that exists within this tissue with greater scrutiny, demonstrating neurovascular interactions, parenchymal innervation, neuroimmune interactions, and neuro-adipose connections. It has been demonstrated previously that the neurites innervating scWAT branch from the same NBs that lead to the skin (Huesing et al, 2021), but we and others have clearly demonstrated that axon endings do terminate inside the parenchyma of scWAT. For the first time, we reveal a terminal junction of axons in scWAT, which we call the neuro-adipose nexus.…”
Section: Articlecontrasting
confidence: 42%
“…White adipose tissue (WAT) is typically associated with energy storage, but is a dynamic and plastic tissue capable of undergoing transformation during the “browning” process (stimulated by negative energy balance states like exercise or cold), which leads to increased presence of brown adipocytes and increased sympathetic neurite outgrowth. WAT is now appreciated to be highly innervated by both sympathetic ( Foster et al., 1982 ; Foster and Bartness, 2006 ; Huesing et al., 2021 ) and sensory nerves ( Fishman and Dark, 1987 ; Bartness et al., 2010 ), but not parasympathetic nerves ( Giordano et al., 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…For iDISCO immunohistochemical staining and tissue clearing, UCP1cre reporter mice were perfused with saline and paraformaldehyde as described earlier (Francois et al, 2019;Huesing et al, 2021) and interscapular BAT was dissected as an entire tissue block keeping core BAT and surrounding WAT intact to maintain the tissue context (n = 5, 5 males). We followed the iDISCO method with modification from (Renier et al 2014) for TH-protein (1:1000, rabbit anti-TH, Millipore, Cat# AB152, RRID:AB_390204) (Meurers et al, 2009), the endothelial marker CD31 (1:300, rabbit anti-CD31, Novus Biologicals, Cat#AF3628, RRID:AB_2161028) (Huesing et al, 2021), and/or GFP reporter (1:400, chicken anti-GFP, Abcam, Cat#ab13970, RRID:AB_300798) (Zhang et al, 2011) as published at protocol.io (dx.doi.org/10.17504/protocols.io.wzuff6w).…”
Section: Immunohistochemistry With Tissue Clearing (Idisco)mentioning
confidence: 99%
“…Sympathetic innervation plays an important role in regulating two key aspects of adipose tissue function: lipolysis and thermogenesis. Dense sympathetic parenchymal innervation is observed in both iBAT and the inguinal region of iWAT, where beige adipocytes are primarily located; however, sparse innervation is found in eWAT and the dorsolateral region of iWAT, an area of the tissue that is devoid of beige adipocytes even under long term cold stimulation (Chi et al, 2018b;Dichamp et al, 2019;Huesing et al, 2020;Murano et al, 2009;Zeng et al, 2019). The strong association between thermogenic adipocytes and dense sympathetic neurites as well as the association between white adipocytes and sparse innervation suggests that adipocyte type may determine the density of sympathetic parenchymal innervation.…”
Section: Discussionmentioning
confidence: 99%